Attitudes towards COVID-19-Related Medical Misinformation among Healthcare Workers and Non-Healthcare Workers in Saudi Arabia during the Pandemic: An Online Cross-Sectional Survey - Amna Abdullah Alotiby (International Journal of Environmental Research and Public Health, 2021)
Since the SARS-CoV-2 virus caused a global pandemic, the amount of misinformation in various media outlets has been on the rise. This has caused confusion among both healthcare workers and the general population about what the proper precautions against COVID-19 are. This study investigated attitudes towards misinformation related to protective measures that can be taken against COVID-19. The study was conducted in Saudi Arabia using an online survey questionnaire during the first three months of lockdown responding to the pandemic. The sample size of the study was N = 1294, of which 275 were healthcare workers and 974 were non-healthcare workers. The findings indicate that the Saudi Arabian population has a “Neutral” attitude towards COVID-19-related misinformation, meaning that, overall, they neither agree nor disagree with the most common COVID-19-related misinformation. Both healthcare workers and non-healthcare workers displayed a “Neutral” attitude towards herbal remedies for COVID-19. The level of agreement regarding the SARS-CoV-2 virus remaining in the throat for two days and the BCG vaccine protecting against COVID-19 was low. The findings of this research imply that knowledge dissemination is severely lacking in Saudi Arabia and that the Ministry of Health in Saudi Arabia should sincerely consider educating healthcare workers better about verified and true information regarding COVID-19. Conclusion: Future research should include larger sample sizes for each of the healthcare specialties surveyed in this study and analyse their attitudes towards COVID-19 misinformation.